Psychopharmacotherapy of Depressive Disorders in Alcoholism - Xayatova Shoira Telmanovna; Xayatov Rustam Batirbekovich (Genius Journals, 2023)
This article presents a paper that examines the relationship of pathological attraction to psychoactive substances with affective disorders. Taking into account the results obtained, the practical experience of therapy of pathological attraction to psychoactive substances using antidepressants is presented. A clinical study with the use of antidepressants was conducted in 44 patients (men – 26, women – 19). The optimal effectiveness of treatment is presented in this article. Depression in patients with alcoholism in most cases of somatogenic origin, i.e. associated with the toxic effect of alcohol on the central nervous system (CNS), and in most patients it spontaneously decreases within 2-4 weeks after the relief of alcohol withdrawal syndrome and abstinence from ethanol.
Keywords: pathological drives; affective disorders; psychoactive substances; mental disorders